Genome-Wide Association Study on Seminal and Nodal Roots of Wheat Under Different Growth Environments - Xu, Fengdan; Chen, Shulin; Yang, Xiwen; Zhou, Sumei; Chen, Xu; Li, Jie; Zhan, Kehui; He, Dexian (Frontiers in Plant Science, 2021)
The root of wheat consists of seminal and nodal roots. Comparatively speaking, less studies have been carried out on the nodal root system due to its disappearance at the early seedling stage under indoor environment. In this study, 196 accessions from the Huanghuai Wheat Region (HWR) were used to identify the characteristics of seminal and nodal root traits under different cultivation environments, including indoor hydroponic culture (IHC), outdoor hydroponic culture (OHC) and outdoor pot culture (OPC), for three growing seasons. The results indicated that the variation range of root traits in pot environment was larger than that in hydroponic environment, and canonical coefficients were the greatest between OHC and OPC (0.86) than those in other two groups, namely, IHC versus OPC (0.48) and IHC versus OHC (0.46). Most root traits were negatively correlated with spikes per area (SN), grains per spike (GPS) and grain yield (GY), while all the seminal root traits were positively correlated with thousand-kernel weight (TKW). Genome-wide association study (GWAS) was carried out on root traits by using a wheat 660K SNP array. A total of 35 quantitative trait loci (QTLs)/chromosomal segments associated with root traits were identified under OPC and OHC. In detail, 11 and 24 QTLs were significantly associated with seminal root and nodal root traits, respectively. Moreover, 13 QTLs for nodal roots per plant (NRN) containing 14 stable SNPs, were distributed on chromosomes 1B, 2B, 3A, 4B, 5D, 6D, 7A, 7B and Un.Based on LD and bioinformatics analysis, these QTLs may contain 17 genes closely related to NRN. Among them, TraesCS2B02G552500 and TraesCS7A02G428300 were highly expressed in root tissues. A conclusion can be drawn that a medium or even slightly smaller root system is probably beneficial for promoting grain yield. Moreover, the frequencies of favorable alleles of these 14 SNPs were confirmed to be less than 70% in the natural population, suggesting that it still is improving the utilization of these superior genes in wheat root.